A framework for consolidating most important digitized Croatian dictionaries from 1595 to 1945 - Bago, Petra (Array, 2012)
The Text Encoding Initiative (TEI) is a consortium which collectively develops and maintains a standard for the representation of texts in digital form. Its chief deliverable is a set of Guidelines which specify encoding methods for machine-readable texts, mainly in the humanities, social sciences and linguistics. The Guidelines have been widely used for online research, teaching, and preservation. Dictionaries are considered one of the most complex text types in TEI because of their high degree of structuring and compression of information [1]. This research deals with most important Croatian printed bilingual and multilingual dictionaries from 1595 to 1945. Currently, all of the dictionaries are in the process of digitization. All pages of the dictionaries have been digitally photographed (most of them in color) in a very high resolution and transformed each into its own text database. The transformation was conducted in three steps. First, the photographs were processed with an OCR software. Second, an automatic method was used to correct some of the mistakes. Third, everything was manually corrected to minimize errors in the documents. All of the dictionaries went through the first and second phase ; a small number of them still have to be manually checked. The aim of this research is to provide an eXtensible Markup Language (XML) platform for selected Croatian printed bilingual and multilingual dictionaries based on TEI: P5 Guidelines for Electronic Encoding and Interchange. The idea is to design a universal structure that would contain all views of TEI Guidelines for each dictionary: the typographic view, the editorial view and the lexical view.